CeO2@NH2 functionalized electrodes for the rapid detection of SARS-CoV-2 spike receptor binding domain - Triastuti, Ayu; Zakiyyah, Salma Nur; Gaffar, Shabarni; Isa Anshori; Surawijaya, Akhmadi; Hidayat, Darmawan; Hesti Lina Wiraswati; Yusuf, Muhammad; Yeni Wahyuni Hartati (RSC advances, 2023)
A detection method based on an electrochemical aptasensor has been developed as an alternative fast, portable, simple, inexpensive, and high-accuracy detection method for detecting the SARS-CoV-2 Spike Receptor Binding Domain (spike RBD). The CeO2@NH2 functionalized Screen Printed Carbon Electrode (SPCE) was used to immobilize an aminated aptamer of spike RBD protein via glutaraldehyde as a linker. The aptamer's interaction with the SARS-CoV-2 Spike RBD was measured via the [Fe(CN)6]4−/3− redox system signal. Experimental conditions were optimized using a Box–Behnken experimental design and showed that the optimal conditions of the SARS-CoV-2 aptasensor were 1.5 ng mL−1 of aptamer, immobilization of aptamer for 60 minutes, and Spike RBD incubation for 10 minutes. The developed aptasensor was able to detect the standard SARS-CoV-2 Spike RBD with a detection limit of 0.017 ng mL−1 in the range of 0.001–100 ng mL−1. This aptasensor was used to detect salivary and oropharyngeal swab samples of normal individuals with the addition of Spike RBD, and the recoveries were 92.96% and 96.52%, respectively. The testing on nasopharyngeal swab samples of COVID-19 patients showed that the aptasensor results were comparable with the qRT-PCR results. Thus, the developed aptasensor has the potential to be applied as a SARS-CoV-2 rapid test method for clinical samples.